ANALYSIS OF THE POSSIBILITY OF BANKRUPTCY IN MEDIUM-SIZED AGRIBUSINESS COMPANIES IN AP VOJVODINA - Jocić, Bogdan; Milić, Dragan; Zekić, Vladislav; Novaković, Dragana; Novaković, Tihomir; Ilić, Zoran (Economics of Agriculture, 2024)
In the context of a volatile economy marked by diverse global crises, it becomes imperative to proactively assess the potential insolvency among economic entities. This study focuses on medium-sized companies involved in agricultural and food production within the AP Vojvodina, spanning the time frame from 2018 to 2022. The primary objective is to assess the likelihood of bankruptcy within the observed companies, applying Altman’s modified Z score (Z’), Kralicek Quick test and the Springate model. The data utilized for this research are sourced from the financial reports of the observed companies. Based on the performed analysis, it can be concluded that the modified Altman’s Z’ score and the Springate model in most cases gave identical results on the occurrence of bankruptcy. Using the Kralicek Quick test, the solvency ratings are quite divergent. In the observed period, the possibility of bankruptcy was higher for agricultural companies compared to ones from the food industry.